Manajemen Pelaksanaan Kurban Di Mahad Al-Zaytun - Mutakin Mutakin; Ahmad Asrof Fitri; Sobirin Sobirin (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This research aims to examine the management process of qurbani implementation in Ma’had Al-Zaytun, an educational institution known for its comprehensive approach to character building and spiritual development. The implementation of qurbani at this institution covers several management functions, including planning, organizing, implementing, and evaluating. The study employs a qualitative approach using a case study method, with data collected through direct observation, in-depth interviews with those involved in qurbani management, and analysis of supporting documents. The findings indicate that the qurbani management process in Ma’had Al-Zaytun is well-organized and systematically executed, upholding Islamic legal principles and promoting values of social solidarity. Effective planning, from selecting appropriate sacrificial animals to determining the slaughter time and location, as well as the meat distribution process, is crucial to the program’s success. The involvement of committees, students, and teachers fosters operational efficiency. However, the study highlights challenges such as coordination issues and distribution management. To address these, it recommends improving training, supervision, and management information systems.